The Effect of Ingesting Coconut Water (Cocos nucifera L.) Mixed with Aren Sugar (Arenga Pinnata) and Isotonic Drinks On Glucose Level, Blood Lactic Acid, and Hydration Status in University Basketball Atheletes - Emir Rizkanto, Billy
Background Carbohydrate ingestion during intermittent exercise with an intensity of more than 75% of VO?max such as basketball must be taken care intensively so that the athletes’performance in the field can be maintained. Coconut water has been known to be used as a good natural isotonic drink. Meanwhile aren sugar contains a high carbohydrate and a low glycemic index, makes it suitable well for sportsmen and people with diabetes. The purpose of this study is intended to find out the effect of giving coconut water drinks mix aren sugar to blood glucose levels, lactic acid levels and hydration status in basketball matches. The results of this study are expected to be developed into natural electrolyte carbohydrate drinks. Method: Subjek in this study were 10 university basketball player use clinical study single-blind crossover design. The parameters measured were blood glucose levels, lactic acid levels. The data then were analysed by using SPSS and Mann Whitney Utest. Result. glucose levels at the end of the second quarter, the experimental group did not differ significantly from the isotonic or control groups, but the control group differed significantly (p <0.05) from the isotonic group. 30 minutes after the match the experimental group had the highest glucose levels (151.6 ± 20.89) and did not differ significantly from the isotonic group (144 ± 32.79), the experimental group differed significantly (p <0.001) with the control group (111, 7 ± 19.03). Lactic acid levels in the experimental group match were lower (5.22 ± 1.51) in the second quarter and (5.23 ± 1.29) in the fourth quarter did not differ significantly from the isotonic group (5.51 ± 2.32) in the in the second quarter and (6.04 ± 2.20) in the fourth quarter, the control group's lactic acid level (8.42 ± 5.46) in the second quarter and (9.42 ± 5.21) in the fourth quarter differed significantly from experimental drinks (p <0.001), urine specific gravity from the three groups did not prove significantly different results, but coconut water mixed with palm sugar had the lowest urine specific gravity value Conclusion. The consumption coconut water mixed with aren sugar can maintain blood glucose levels and delay fatigue quite well, thus drink can be a replacement solution for isotonic drinks from natural ingredients that are relatively safe